The Russian Constitution of 1993 and the Constitutionalization of Federal Legislation: Data Analysis - S. Popova; A. Yanik (BRICS Law Journal)
The Constitution of the Russian Federation of 1993 provided the basis and tools for large-scale societal transformations in Russia. Still, the question of whether the results of political and socio-economic reforms are irreversible and in line with constitutional ideas and norms is open to discussion. This study investigates the temporality of the process of the “constitutionalization” of Russian law using the statistics of Federal laws and Federal constitutional laws for the period 1994–2018. The article presents the outcome of the quantitative analysis as well as a discussion of the findings involving the approaches of the legal and political sciences. The research leaves open the question of the relationship between the durability of the democratic constitution and the quality and irreversibility of democratic transformations of the social system. Monitoring the dynamics of the adoption of primary laws and laws on amendments gives evidence that even a “rigid” democratic constitution can become “elastic” with age since its ideas and meanings can often be “stretched” to apply to current cases without the need to make any changes to existing constitutional norms. The authors propose considering the conceptual possibilities of adaptive governance theory to explain the features of modern Russian lawmaking (“adaptive lawmaking,” “agile lawmaking”).